2018
DOI: 10.1063/1.5023103
|View full text |Cite
|
Sign up to set email alerts
|

An empirically-based model for the lift coefficients of twisted airfoils with leading-edge tubercles

Abstract: Experimental data for untwisted airfoils are utilized to propose a model for predicting the lift coefficients of twisted airfoils with leading-edge tubercles. The effectiveness of the empirical model is verified through comparison with results of a corresponding computational fluid-dynamic (CFD) study. The CFD study is carried out for both twisted and untwisted airfoils with tubercles, the latter shown to compare well with available experimental data. Lift coefficients of twisted airfoils predicted from the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…However, the CVPs cannot ensure a completely attached flow regime throughout the tubercle airfoil span. Several researchers have additionally reported the intermittent appearance of large separation zones or stall cells 4,13,25,30,38 on the tubercle airfoil. Interestingly, it has been found that the development of these CVPs and stall cells depends on parameters like A, k, and a.…”
Section: Introductionmentioning
confidence: 99%
“…However, the CVPs cannot ensure a completely attached flow regime throughout the tubercle airfoil span. Several researchers have additionally reported the intermittent appearance of large separation zones or stall cells 4,13,25,30,38 on the tubercle airfoil. Interestingly, it has been found that the development of these CVPs and stall cells depends on parameters like A, k, and a.…”
Section: Introductionmentioning
confidence: 99%